Tinjauan Kritis terhadap Ketentuan Tindak Pidana Penghinaan Presiden dalam Kuhp Baru dalam Perspektif Kebebasan Berpendapat - Abdul Rahman; Budi Sastra Panjaitan; Arifuddin Muda Harahap (Pusat Riset dan Inovasi Nasional, 2025)
The enactment of Law No. 1 of 2023 concerning the Criminal Code (KUHP) has brought a number of controversies, one of which is related to the revival of provisions regarding the criminal act of insulting the President and Vice President. This article aims to critically examine these provisions in the perspective of the freedom of expression guaranteed by the Indonesian constitution and international human rights instruments. This research uses a normative juridical approach with an analysis of the norms in the new Criminal Code, the 1945 Constitution, as well as international treaties such as the International Covenant on Civil and Political Rights (ICCPR). The results of the study show that although the provision of insulting the President in the Criminal Code is only referred to as a complaint offense and is framed to protect the dignity of state institutions, the provision still has the potential to limit freedom of opinion excessively. In addition to risking opening a loophole for criminalization of legitimate public criticism, this rule also has the potential to contradict the principles of non-discrimination and accountability of public officials in a democratic country. Therefore, an in-depth evaluation of the formulation of norms and their application is needed so that they do not conflict with the spirit of democracy and the protection of human rights. Keywords: , , , , .